FAKTOR YANG MEMPENGARUHI MOTIVASI DONOR DARAH SUKARELA DI UDD PROVINSI SULAWESI UTARA - Intan Simatupang; Agustevie Telew; Lucyana Pongoh (Yayasan Syalom Cipta Sumikolah, 2025)
Blood donation is an important humanitarian activity in meeting the need for transfusion blood, especially in Indonesia, which still faces a shortage of blood supply. This study aims to identify the factors influencing the motivation of voluntary blood donors at the PMI of North Sulawesi Province, focusing on the relationship between knowledge, attitudes, and individual characteristics towards blood donation motivation. This study uses an analytical method with a cross-sectional design involving 96 respondents. Data were collected through questionnaires and analyzed using the Chi-square test. The research results show a significant relationship between knowledge (p = 0.003) and attitude (p = 0.003) with blood donation motivation. Respondents with good knowledge and positive attitudes tend to have higher motivation to donate blood voluntarily. These findings indicate that education and positive campaigns can increase voluntary blood donation participation. This research makes an important contribution to the development of strategies to increase blood donor participation, including through educational programs, information campaigns, and the reinforcement of positive attitudes towards blood donation. These efforts are expected to support the adequate availability of blood for transfusion needs in North Sulawesi Province.